Fire, Fuel, and Climate Interactions in Temperate Climates - Stephanie K. Kampf; Camille S. Stevens‐Rumann; Leónia Nunes; Ana Catarina Sequeira; Francisco Castro Rego; Cristina Fernández; Ana Hernández‐Duarte; Clara E. Mosso; Jean Pierre Francois; Alejandro Miranda (AGU Advances)
Abstract Temperate regions around the world are experiencing longer fire weather seasons, yet trends in burned area have been inconsistent between regions. Reasons for differences in fire patterns can be difficult to determine due to variable vegetation types, land use patterns, fuel conditions, and human influences on fire ignition and suppression. This study compares burned areas to climate and fuel conditions in three temperate regions: the desert, shrub, and forest ecoregions of western North America, west‐central Europe, and southwestern South America. In each region the mean annual aridity index (AI, precipitation over potential evapotranspiration) spans arid to humid climates. We examined how the fraction of area burned from 2001 to 2021 varied with mean annual AI, mean aboveground biomass, and land cover type distributions. All three regions had low fractions of area burned for the driest climate zones (AI < 0.5), a sign of fuel limitation to burned area. Fraction of area burned increased with mean aboveground biomass for these dry zones. Fraction of area burned peaked at intermediate AI (0.7–1.5) for all regions and declined again in the wettest climate zones (AI > 1.5), a sign of climate limitation to burned area. Of the three regions, western North America had the highest burned area, fraction of area burned, and fire sizes. Fragmentation of vegetation patches by the high Andes Mountains in southwestern South America and by intensive land use changes in west‐central Europe likely limited fire sizes. All three regions are at risk for future wildfires, particularly in areas where fire is currently climate limited.